2008
DOI: 10.1016/j.vaccine.2007.11.087
|View full text |Cite
|
Sign up to set email alerts
|

Selection and evaluation of the immunogenicity of protective antigen mutants as anthrax vaccine candidates

Abstract: Protective antigen (PA) is a central component of anthrax toxin and a major antigen in anthrax vaccines. However, the use of native PA as a vaccine is not optimal. If administered to people who have been freshly exposed to anthrax, PA may actually aid in anthrax toxin formation and thus may pose a serious safety concern for postexposure vaccination applications. A non-functional PA mutant may be much safer alternative. To identify an improved anthrax vaccine antigen, we examined four non-functional mutants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
1
17
1
Order By: Relevance
“…Analysis by 3% to 20% native PAGE showed that all SA formed complexes with DSbt at a ratio of 2:1 (DSbt:SA ratio) (data not shown). To test the adjuvant effect of DS, mouse antibody responses to immunizations with pneumococcal type 14 capsular polysaccharide (Pn14) (10 g) and Pn14ϩDS mixture (10 ϩ 10 g) or to a mutant protein of the anthrax toxin protein PA (DNI) 10,11 (10 g) and DNIϩDS mixture (10 ϩ 10 g) were compared. Pn14 was purchased from the American Tissue Culture Collection and purified as described.…”
Section: Mouse Immunizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis by 3% to 20% native PAGE showed that all SA formed complexes with DSbt at a ratio of 2:1 (DSbt:SA ratio) (data not shown). To test the adjuvant effect of DS, mouse antibody responses to immunizations with pneumococcal type 14 capsular polysaccharide (Pn14) (10 g) and Pn14ϩDS mixture (10 ϩ 10 g) or to a mutant protein of the anthrax toxin protein PA (DNI) 10,11 (10 g) and DNIϩDS mixture (10 ϩ 10 g) were compared. Pn14 was purchased from the American Tissue Culture Collection and purified as described.…”
Section: Mouse Immunizationsmentioning
confidence: 99%
“…12 DNI was prepared as previously described. 10,11 ELISA Specific and total IgM or IgG (including IgG isotypes) were measured by ELISA in cell culture supernatants or in immunized mouse sera. The following antigens and concentrations were used for plate coating: SA, 10.0 g/mL; Pn14, 20.0 g/mL; histones (unfractionated from calf thymus; Sigma), 25.0 g/mL; double-stranded DNA (dsDNA; activated calf thymus DNA, Sigma), 20.0 g/mL; single-stranded DNA (ssDNA), 20.0 g/mL; goat F(ab') 2 anti-mouse immunoglobulin, 2.5 g/mL; DS-BSA conjugate, 10.0 g/mL; DNI, 5.0 g/mL; and DS, 20.0 g/mL.…”
Section: Mouse Immunizationsmentioning
confidence: 99%
“…Therefore, nonfunctional PA DNI mutants may be an ideal substitute for WPA in a potential vaccine against anthrax. This theory was confirmed by evidence showing that double mutation, K397D and D425K, of PA not only rendered PA mutants nonfunctional but also enhanced their immunogenic potency in mice (1,33,35,44). Phenylalanine-427 of PA is another candidate site for mutation because it is crucial for the transport function of PA, being involved in both pore formation and protein translocation (41).…”
Section: Discussionmentioning
confidence: 86%
“…This is called the dominant-negative inhibitory (DNI) phenotype. In protection against anthrax, the induction of a DNI phenotype may be advantageous since a stronger immunogenic effect than that with WPA is obtained (1,44). Therefore, postexposure use of PA DNI mutants may provide improved immunogenicity and therapeutic activity simultaneously.…”
mentioning
confidence: 99%
“…Because infections are highly fatal, the organisms are easily produced, and the spores spread easily, B. anthracis has been used as a bioweapon in biological war and biological terrorism (38). If inhaled, the spores are phagocytosed by alveolar macrophages, where they germinate to produce vegetative bacteria (10,24).…”
mentioning
confidence: 99%